PENINGKATAN HASIL BELAJAR MELAL UI MODEL COOPERTIVE LEARNING TOGETHER PELAJARAN KESEIMBANGAN DAN PELESTARIAN SUMBER DAYA ALAM KELAS IVB SD N KESTALAN SURAKARTA 2021/2022 - Safira Gusta Ayustina; Mukhlis Mustofa (Universitas Negeri Medan, 2021)
Abstract : Learning outcomes through cooperative learning together: SD Negeri Kestalan No.05. The purpose of the study was to improve learning outcomes by using the cooperative learning together learning model at SD Negeri Kestalan No. 05 Surakarta. The subjects in this study were male and female students in the fourth grade of SD Negeri Kestalan No. 05 Surakarta. The target number is 18 students, 10 participants are male students and 8 female students. Data collection techniques using: interviews, tests and observations, in this study the researchers made 2 cycles, each cycle consisting of one meeting. In this study, it was shown that children's learning outcomes using the cooperative learning model learning together experienced an increase of up to 70% from the previous one. By changing the learning model with the cooperative learning model, children become more happy to learn because this model is the same as the group learning model. Keywords: learning outcomes, Cooperative learning together Abstrak : Hasil belajar melalui model pembelajaran cooperative learning together: SD Negeri Kestalan No.05. Tujuan penelitian adalah meningkatkan hasil belajar dengan menggunakan model pembelajaran cooperative learning together di SD Negeri Kestalan No.05 Surakarta. Subjek dalam penelitian ini adalah peserta didik laki-laki dan perempuan kelas IV SD Negeri Kestalan No.05 Surakarta. Jumlah sasaran sebanyak 18 peserta didik, 10 pesera didik laki-laki dan 8 peserta didik perempuan. Teknik pengumpulan data dengan mengggunakan: wawancara, tes dan observasi, dalam penelitian ini peneliti membuat dengan 2 sikluus yang setiap siklusnya terdiri dari satu pertemuan. Dalam penelitian ini menunjukkan bahwa hasil belajar anak dengan menggunakan model belajar cooperative learning together mengalami peningkaatan hingga 70% dari sebelumnmya. Dengan mengubah model belajar dengan model cooperative learning together anak menjadi lebih senang belajar dikarenakan model ini sama halnya dengan model belajar kelompok. Kata kunci: Hasil belajar, Cooperative learning